Acting in time on energy policy - Gallagher, Kelly Sims. (Brookings Institution Press, 2009)
"Details the often incomplete, incoherent, and ineffectual U.S. energy policy, tackling specific policy questions: Why are these components of energy policy so important? How would 'acting in time'--not waiting until politics demands action--make a difference? What should our policy actually be? Proposes measures to overcome this counterproductive tendency"--Provided by publisher.